МІЖНАРОДНІ СТАНДАРТИ ЗАБЕЗПЕЧЕННЯ ПРАВА ДОСТУПУ ДО СУДУ УЧАСНИКАМ ЕКОНОМІЧНИХ ВІДНОСИН - Koverznev, V.O. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2020)
Transformation and sustainable development of modern countries is not possible without providing all participants in economic relations with equal access to justice, which should be based on respect for fundamental rights, the Rule of Law, transparent courts and the effective administration of justice, guaranteeing public access to information about activity of commercial courts. The term "access to court" is a complex legal category based on several basic criteria, the simultaneous provision of which guarantees the actual observance of a person's right to access to justice, in particular: 1) financial, which provides for the obligation of the state to establish such an algorithm for determining the amount of court costs, which takes into account the property of the party and does not create obstacles to the exercise of the right to go to court, while acting as a safeguard against abuse of the right to go to; 2) territorial, which provides that the system of courts of general jurisdiction should be built taking into account the territorial structure of the state, with local courts, which consider all cases as courts of first instance, should be territorially as close as possible to the person; 3) organizational — provides for the optimal organization of the judicial system, which should be simple and, at the same time, clear and effective, in the context of access to court and the procedure for protection of individual rights. In addition, both the system of general courts as a whole and each individual court of general jurisdiction must be established and carry out their procedural activities in strict accordance with national law; 4) informational, according to which each state must legislate to inform its citizens and business entities about the procedure for going to court, about the conditions of providing certain categories of socially vulnerable citizens engaged in business activities, professional legal assistance provided by lawyers at the expense of the state, as well as the cur rent procedural rules; 5) procedural, which guarantees the administration of justice on the basis of the Rule of Law, as well as impartiality and impartiality of the court and judges, reasonable timeliness of court proceedings, publicity of proceedings and promulgation of court decisions, proper motivation and justification of court decisions, ensuring effective execution of court decisions and respect for final court decision; 6) quality of legislation, which imposes on the state the obligation to adopt legislation that meets the requirements of accessibility and predictability, so that each person has the opportunity to obtain adequate information about the circumstances of the application of legal norms in a particular case. REFERENCES